2019
DOI: 10.1186/s12877-019-1181-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria in older adults: the most fragile women are prone to long-term colonization

Abstract: Background The diagnosis of urinary tract infections (UTIs) in institutionalized older adults is often based on vague symptoms and a positive culture. The high prevalence of asymptomatic bacteriuria (ABU), which cannot be easily discriminated from an acute infection in this population, is frequently neglected, leading to a vast over-prescription of antibiotics. This study aimed to identify subpopulations predisposed to transient or long-term ABU. Methods Residents in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…Out of 180 urine samples collected during this study, 82 (45.5%) patients had urine samples with significant bacteriuria and asymptomatic bacteriuria was more prevalent (71%), specifically in males more than females; our findings confirmed by Nicolle et al [21] who concluded that asymptomatic bacteriuria in older is common. The majority of participants were male (61%), this is more or less near to Biggel et al [22], although it conflicts with previous studies [23,24] and a general knowledge state that the prevalence of bacteriuria is approximately 3 times higher in female than male elderly populations. A general conclusion verified that female patients due to their genital anatomy were more predisposed to urinary infection.…”
Section: Discussioncontrasting
confidence: 85%
“…Out of 180 urine samples collected during this study, 82 (45.5%) patients had urine samples with significant bacteriuria and asymptomatic bacteriuria was more prevalent (71%), specifically in males more than females; our findings confirmed by Nicolle et al [21] who concluded that asymptomatic bacteriuria in older is common. The majority of participants were male (61%), this is more or less near to Biggel et al [22], although it conflicts with previous studies [23,24] and a general knowledge state that the prevalence of bacteriuria is approximately 3 times higher in female than male elderly populations. A general conclusion verified that female patients due to their genital anatomy were more predisposed to urinary infection.…”
Section: Discussioncontrasting
confidence: 85%
“…Conversely, a substantial fraction of the present cystitis and ABU isolates, including strains that asymptomatically colonized the urinary tract over months 53 , carried papGII , without causing invasive infection. Apart from possible stochastic effects, this may reflect in part the known variation in host susceptibility to UTI in relation to specific host genetic polymorphisms 54 ; conceivably, these isolates’ corresponding source hosts may have been more resistant to developing invasive UTI.…”
Section: Discussionmentioning
confidence: 88%
“…Most of the isolates originated from female participants (41/42) with incontinence (39/41). A comprehensive analysis of bacteriology and risk factors associated with ABU at one of the two collections sites was published previously 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Asymptomatic bacteriuria is the presence of bacteria in a urine sample from a patient that shows no signs or symptoms originating from the urinary tract [ 12 ]. Positive urine tests in the nursing home population are common because the frequency of asymptomatic bacteriuria varies between 40–80% among nursing home residents [ 9 , 13 ]. The evidence states that this patient group will not benefit from antibiotic treatment of asymptomatic bacteriuria.…”
Section: Introductionmentioning
confidence: 99%